Hepatic Encephalopathy is Associated With Slow Speech on Objective Assessment. (2nd September 2021) - Bloom, Patricia P.; Robin, Jessica; Xu, Mengdan; Arvind, Ashwini; Daidone, Michael; Gupta, Anoopum S.; Chung, Raymond T.
Abstract : Introduction: There are no available low-burden, point-of-care tests to diagnose, grade, and predict hepatic encephalopathy (HE). Methods: We evaluated speech as a biomarker of HE in 76 English-speaking adults with cirrhosis. Results: Three speech features significantly correlated with the following neuropsychiatric scores: speech rate, word duration, and use of particles. Patients with low neuropsychiatric scores had slower speech (22 words/min, P = 0.01), longer word duration (0.09 seconds/word, P = 0.01), and used fewer particles (0.85% fewer, P = 0.01). Patients with a history of overt HE had slower speech (23 words/min, P = 0.005) and longer word duration (0.09 seconds/word, P = 0.005). Discussion: HE is associated with slower speech. Abstract :